Determination of Cadmium(II) Using Cd(II)-Imprinted Nano Diazoaminobenzene-Vinylpyridine Copolymers - Javad Poursharifi, Mohamad; Moghimi, Ali (Asian Journal of Chemistry, 2012)
Cd(II) imprinted and non-imprinted copolymers were prepared by metal ion imprinted polymer (MIIP) technique. The copolymers were obtained by copolymerizing cadmium chloride (or without it), nano diazoaminobenzene (DAAB) and vinylpyridine (VP) using ethyleneglycoldimethacrylate (EGDMA) as cross-linker in presence of 2,2'-azobisisobutryonitrile as initiator. The separation and preconcentration characteristics of the copolymers for Cd(II) were investigated by batch and column procedures. The results demonstrated that the Cd(II) imprinted copolymers had higher adsorption capacity with the value of 205 μmol g-1 of dry copolymer, ca. 3.5 times and good selectivity for Cd(II) compare to non-imprinted copolymers (58.6 μmol g-1 of dry copolymer). The distribution ratio (D) values of the Cd(II) imprinted copolymers increased for Cd(II) with respect to both D values of Zn(II), Cu(II), Fe(II) and non-imprinted copolymer. The relatively selective factor (ar) values of Cd(II)/Cu(II), Cd(II)/ Zn(II), Cd(II)/Fe(II), are 36.7, 51.8, 86.7, respectively. The tolerance limit for other electrolytes such as NaCl, KBr, KI, NaNO3, Na3PO4, Na2SO4 and Mg(NO3)2 is also greatly improved with the values of 10-100-fold of the non-imprinted copolymer. The Cd(II) imprinted copolymers can be used at least 20 times with recoveries no less than 96 %. Based on the packed columns with Cd(II) imprinted copolymers, a highly selective solid-phase extraction (SPE) and preconcentration method for Cd(II) from dilute aqueous solution was developed. The MIIP-SPE preconcentration procedure showed a linear calibration curve within concentration range from 0.13-25 μg L-1. The detection limit and quantification limit were 0.05 and 0.13 μg L-1 (3s) for graphite furnace atomic absorption spectrometry (GF AAS). The relative standard deviation of the eleven replicate determinations was 2.6 % for the determination of 1 μg of Cd(II) in 100 mL water sample. Determination of Cd(II) in certified tap water and rain water demonstrated that the column was good enough for Cd(II) determination in matrixes containing components with similar chemical property such as Cu(II), Zn(II), Fe(II).